Phonetic Analysis of Makhārij al-Ḥurūf Pronunciation Errors in the Recitation of Surah Al-Fātiḥah by Grade VIII Students at SMPIT Nurul Yaqien: English - haryadi, alfin maulana; Marlina, Lina (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to analyze phonetic errors in makharij al-ḥurūf (the articulation points of Arabic letters) in the recitation of Surah Al-Fātiḥah by 8th-grade students of SMPIT Nurul Yaqien. The method used is descriptive qualitative, involving direct observation and in-depth interviews with tahsin teachers and selected students. The results show that the most frequent pronunciation errors occurred in the letters Ḍād (ض), Ṣād (ص), Ghain (غ), Ḥā’ (ح), and ‘Ain (ع), which have no direct equivalents in Indonesian phonology. Contributing factors include limited theoretical understanding of makhraj, lack of articulation practice, and teaching methods that do not incorporate phonetic-based approaches. The findings highlight the need for phonetic and visual strategies in teaching tajweed to improve mastery of makharij al-ḥurūf. Theoretically, this study contributes to Arabic linguistic research by identifying phonetic error patterns among non-native speakers. Practically, it serves as a foundation for developing more effective phonetic-articulatory based tajweed instruction methods in Islamic educational institutions.